PROBING – PROMPTING LEARNING MODEL IN ENHANCING STUDENTS’ ENGLISH SPEECH TEXT WRITING SKILL AT POLITEKNIK UNGGUL LP3M - Hermansyah, Hermansyah (JURNAL ILMU PENDIDIKAN, 2024)
This study aims to find out how the Probing-Prompting learning model in enhancing the students’ ability in writing English speech text at Politeknik Unggul LP3M in academic year 2023/2024. This study used an experimental method using cluster random sampling. Class AK-AP2A/23 consisting of 27 students was used as the experimental class, meanwhile class AK-AP2B/23 consisting of 30 students was used as the control class. Based on the research, the test scores for the ability to write speech scripts using the probing-prompting learning method of students in the experimental class showed that the average ability was 83 with the lowest score was 67 and the highest score was 94, having a median value was 82.3 and mode was 83.6. While the ability to write speech text using the expository model in students as the control class was fair. It is indicated by the results of the t-test with a significance level of 0.05, namely t-count 5.00 is greater than t-table 2.026, so H0 is rejected and Hi is accepted.